Approaches to well-being, use of psychology and paternalism in economics - Marion Collewet (Kiel Institute for the World Economy (IfW), 2014)
This paper discusses three approaches to well-being in economics which use insights from psychology to support their position: Scitovsky's Joyless Economy, happiness economics, and the constitutional approach to happiness in economics. It shows that in the way these approaches make use of psychology, normative choice is involved, and there is room for personal judgement. First, an approach to well-being, as an approach to what is worth pursuing, is necessarily normative. The use of psychological theories to support an approach to well-being relies on a normative step, revealed by the choice of a psychological theory by the economist. Second, personal judgement is often needed to translate the findings of psychology to recommendations for practice. Both things have implications for those theories which define well-being as something different than the fulfillment of individual preferences whatever they are, and therefore yield potential for paternalism. The paternalistic recommendations derived by economists are not based on positive science only, but also rely on personal judgement and normative choice.
Keywords: I31; D71; B21; 330; paternalism; well-being; Scitovsky; happiness economics; constitutional approach